Analisis Eksistensi dan Ketunggalan Solusi Model Epidemi SEIR - Roni Tri Putra (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
In this paper, it will be studied existence and uniqueness solution of equilibrium points for a SEIR model with infectious force in latent, infected and immune period. From the model it will be found investigated the existence and uniqueness solution of points its equilibrium. Existence solution of points equilibrium proved by show its differential equations system of equilibrium continue, and uniqueness solution of points equilibrium proved by show its differential equation system of equilibrium differentiable continue.